Improving Students’ Motivation and Speaking Skill through Negotiated Materials at Management Students in University of Pasir Pengaraian, Rokan Hulu, Riau - Pipit Rahayu (Proceedings of ISELT FBS Universitas Negeri Padang, 2014)
The purpose of this research was to improve the students’ motivation and speaking skill through negotiated materials. Negotiated materials means that materials come from discussion by Lecturer and students and these negotiated materials which are based on their students’ study program (Management). Motivation means those students’ effort plus desire in speaking activity or in other words students’ motivation in speaking. While speaking skill means that the capacity of the students to present their materials in front of the class. The participants of this research were the Second Semester students of Management Study Program at University of Pasir Pengaraian, Rokan Hulu, Riau. This class consisted of 38 students. One of the English Lecturer took part in this research as collaborator to assist the implementation of Negotiated Materials, particularly in observing the students’ activities in the teaching and learning process. The method of this research is classroom action research that consisted of three cycles with nine meetings for each. The data were collected through observation checklist, interview, field notes and test.Based on the data analysis of three cycles, it can be concluded that the Negotiated Materials could better improve the students’ motivation and speaking skill. The speaking skill of the students was improved and the students could be involved in teaching and learning process, they became creative, they asked more questions, worked independently and has more aspirations. In addition, Negotiated Material can make the condition of teaching and learning process more communicative as well